Efektivitas Penerapan Multimedia Animaker Dalam Meningkatkan Motivasi Belajar Bahasa Inggris Siswa Sanggar Bimbingan - Anitiara Rufikah, Deliya; Heriyana, Tio; Abdul Manan, Nanan; Hadiana, Oman; Astria Nur, Hana (PGSD Universitas Muhammadiyah Cirebon, 2025)
The research we conducted was motivated by the low learning motivation of students at Sanggar Guidance Subang Mewah Selangor Malaysia in learning English. This research aims to determine the effectiveness of implementing multimedia animaker in increasing motivation to learn English. The research method used in this research is pre-experimental with a one group pretest and posttest design. The research sample consisted of 32 students from class I to class V, and the sampling technique was total sampling. The research instrument used was a questionnaire in order to measure the level of student learning motivation, and the data analysis technique used a paired sample test. The research results we obtained from the pretest with an average score of 28, while the average posttest score was 42. With a total of 884 pretests and a total of 1353 posttests. The use of animation in the learning process is a supporting element to increase learning motivation and make it easier for teachers to enrich the material. teach by utilizing technology. The responses given by students and teachers to the application of animaker in English learning were positive. So that after using animaker, students are able to play an active role, feel pleasure and enthusiasm so that the learning process runs effectively. So from processing this data it can be concluded that the application of multimedia animaker has had a significant impact on increasing motivation to learn English among students at Sanggar Guidance Subang Mewah Selangor Malaysia. Keywords: Multimedia, animaker, student learning motivation